Social customer relationship marketing: A comparative content analysis of Facebook posts between two mobile telecommunication companies - Ting, Zhao Ying (2019)
Facebook is a social networking site that attracts and engages millions of users globally. Due to its interactive nature, companies are now able to communicate with Facebook users via their official pages. This research is an exploratory content analysis that focuses on the Facebook posts of two mobile telecommunication companies in Malaysia. It archives and analyses Facebook posts made by these two companies in May 2015 and May 2016, and further compares them. The findings displays that both companies show significant changes in their posting strategy after a year. This research also categorises the comments from Facebook users and observes how company representatives responded to the comments. From the findings, it can be concluded the two companies have developed their own posting strategy and comment-replying practices on their Facebook pages within the two years.